Blokes talking with blokes: feasibility of a ‘dads-only’ session within an Australian parent education programme - Hauck, Yvonne; Cooper, C.; Lewis, L.; Gibson, R.; Ronchi, F.; Foley, J. (Ten Alps Publishing, 2015)
Background. A man’s transition to fatherhood is recognised as having a significant psychological impact on his life, identity, and state of mind. If men are feeling marginalised, ignored and unable to meet expectations of their support role, health services need to actively involve men, so that they can adjust to one of the important changes in their lives. Aim. A feasibility study was undertaken to determine the acceptability and influence of a fathers-only education session facilitated by a male midwife, on parents’ anxiety, depression, stress and parenting confidence. Men’s resource preferences and feedback in relation to the usefulness of parent education content was collected. Method. A longitudinal comparative design was used to compare Depression, Anxiety and Stress Scales (DASS) scores prior to parent education and six weeks post-birth. Parental self-efficacy and satisfaction scores were collected at follow up. The study context included parent education offered through midwifery-led care models for women attending an Australian tertiary maternity hospital. Parents received a ‘dads-only’ intervention session or the standard programme (comparison group). Ethical approval (No. 514QK) was obtained from the quality improvement and human research ethics committees at the study setting. Results. Of the 115 males recruited, 68 (59%) received the intervention and 47 (41%), the standard programme. Feedback confirmed the session was valued by men. At the six-week post-birth follow up, only 45 men provided DASS and parenting data; 21 (47%) had received the intervention and 24 (53%) the standard programme. Based on a within-group analysis, DASS scores significantly decreased for both groups. Although fewer men in the intervention group at six weeks post-birth had normal anxiety and stress scores, the loss to follow up and small numbers suggest caution in interpreting these results. A common thread of the preferred resources focused upon the parental relationship, practical advice and links to online information. At follow up, parenting satisfaction and self-efficacy scores were comparable between groups. Conclusions. The intervention was acceptable and useful to men. Loss to follow up was a limitation. The suggestion that a one-off session can influence depression, anxiety and stress scores and parental confidence was unsupported. Feedback on content around parenting and lifestyle, infant care and men’s preferred resources may assist in the provision of father-inclusive parent education.